The Criminal Law Enforcement Against Crime Of Carding In Electronic Transactions - Cemban Galuh Sambodo; Sri Endah Wahyuningsih (Law Development Journal, 2021)
The approach method used in this research is normative juridical. This study uses a normative juridical research method using a literature study approach (library research) and statutory approach (statute approach) which in this case is related to Criminal Law Enforcement against Crime of Carding in Electronic Transactions. The data used in this study consists of primary data, secondary data, and tertiary data which will then be analyzed qualitatively. The results of this study indicate that the enforcement of criminal law against the crime of carding as a crime that uses technology is one type of crime that is transnational in nature, it is necessary to have rules that have broad jurisdiction, or an agreement with other countries is needed to be able to arrest and punish the perpetrators criminal acts in the jurisdiction of the State that has an international agreement with Indonesia and, law enforcement officers, adequate human resources are required, so the law enforcement officers can maximum to handle the criminal on the carding in electronical transactions.